If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 4x = -15 Solving -3 + 4x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4x = -15 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = -15 + 3 4x = -15 + 3 Combine like terms: -15 + 3 = -12 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| t-14=12 | | 6-6x=0 | | 8x-1=25 | | 3(-x)-(-2+x)=2x-4 | | 2x^3-11x+18x-9=0 | | -4x+8=16 | | 2x-5=-3 | | (3x-1)+7=8x-(3-2x) | | 2h-6+20=-4 | | 9-2c+c=-13 | | x+2x+(2x+20)=200 | | 8(2p-4)-3p=20 | | 60x^2+x=10 | | X^2-18x+9=0 | | 3x+20+2x-25+5x+10=180 | | C=CM | | 1x+6+2x=15 | | 5t-9=17 | | x+19=2x-(x-19) | | -7x+8=71 | | 0.5(4x-5)=.25(8x+9) | | 4y+5+3=35 | | 5b(4+2)=2x+12 | | 2x+1=23 | | 4x^2+20x-280=0 | | 1=x+1 | | t(7t)= | | 11x^8+11x-110=0 | | 9x+2x+7x=180 | | 4+(y+5)+3=35 | | 28x=12x-7 | | 2n+7= |